Suplementação oral com óleos de linho e peixe para o tratamento da ceratoconjuntivite seca em cães - Guberman, Úrsula Chaves [UNESP] (2015)
The keratoconjunctivitis sicca (KCS) is inflammatory and a common disease in dogs. The use of omega 6 and 3 for treatment in humans and rabbits has been researched because of the potential immunomodulatory effect of these fatty acids, but there are no reports of its use in dogs with this condition. The aim of this study was to investigate the effect of linseed oil and fish oil, products rich in omega 3 and 6, administered orally on tear production and ocular inflammation in dogs with KCS. For this study we used 45 dogs: 15 without KCS, constituting the control group (CG) and 30 with KCS. A randomized, double-blind clinical study was performed in assigned to treatment orally with oil fish (FO) or linseed oil (LO), both once daily for 60 days. More 15 dogs with no KCS were evaluated for a control group (CG). Clinical examination of the eye, Schirmer tear tests I, tear film breakup time, fluorescein test were performed prior to treatment (M0) and at days 15 (M15), 30(M30), 45(M45) and 60(M60) after initiation of treatment. The impression cytology on ocular surface was performed at M0, M30 and M60. The conjunctival histopathological analysis was only performed prior to treatment and at day 60 after treatment. That was a significant decrease in conjunctival hyperemia in dogs of both treatments at day 60. The histopathological analysis revealed a decrease in the epithelial thickness both in FO and LO, a decrease on the degree of keratinization in LO and a decrease inflammatory cell infiltration in FO. There were no significant differences in the others evaluations in both groups. The analyzed results demonstrate that although both treatments administered orally do not increase tear production within 60 days of treatment, it improve the ocular surface. Thus, fish oil reduces eye inflammation. Therefore, treatment with linseed oil or fish may be indicated as adjunctive therapy for dogs with KCS